ANALISIS PRINSIP SYARIAH DAN TEORI KEUANGAN MODERN PADA MANAJEMEN RISIKO PEMBIAYAAN BANK SYARIAH DAN BANK KONVENSIONAL - Junaidi, Ahmad; Fatimah; Maysarah, Siti; Muslimah, Tiara; Setyanoor, Erwan (Ahsan: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2025)
This research analyzes risk management in Islamic and conventional banks in Indonesia using a comparative method. Qualitative data were obtained through an extensive literature review, while quantitative data were derived from the official financial statements of selected banks. The analysis covers various types of risks, including credit risk, liquidity risk, and operational risk, which are critical to banking stability. The findings reveal that Islamic banks, operating under Sharia principles, tend to demonstrate greater stability and resilience compared to conventional banks during financial crises. Although they face challenges in liquidity management and regulatory compliance, Islamic banks perform better in maintaining adequate capital ratios and promoting ethical financing practices. In contrast, conventional banks excel in profitability and revenue generation. Understanding these distinctions is essential for enhancing risk management practices in both banking systems. The results suggest that implementing strategies tailored to the unique characteristics of each banking model can improve financial performance and ensure long-term stability in Indonesia’s banking sector.